BELAJAR TARI TRADISIONAL DALAM UPAYA MELETARIKAN TARIAN ASLI INDONESIA - Jamalul Lail (UII, 2015)
Efforts to preserve the national culture through traditional dances should beencouraged, especially in children. This reason makes writer interested in doing community service programs in the form of traditional dance training for dusunSentono. It is given because children nowadays have only bit understanding about traditional dance.